2015
DOI: 10.1007/s13197-015-2098-3
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of compositional and structural properties in probiotic sausage production

Abstract: In this study, the effects of different fat levels and different particle sizes on compositional and structural characteristics of probiotic fermented sausage were investigated. In order to obtain probiotic character, Lactobacillus casei CRL431 was added. The physicochemical, microbiological and sensory analysis were done. The effect of fat level x mincer hole diameter interaction on hardness values were statistically significant (p < 0.005). At the end of the fermentation-ripening period, L.casei CRL-431 coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 24 publications
2
10
0
1
Order By: Relevance
“…). Similar results were reported by Bagdatli and Kudakci who found the mean scores for surface appearance, surface color, taste, aroma, texture, and overall acceptability of probiotic fermented sausages were above 7 (9‐scale) at the end of the fermentation (14 days). In addition, Neffe‐Skocinska et al .…”
Section: Resultsmentioning
confidence: 99%
“…). Similar results were reported by Bagdatli and Kudakci who found the mean scores for surface appearance, surface color, taste, aroma, texture, and overall acceptability of probiotic fermented sausages were above 7 (9‐scale) at the end of the fermentation (14 days). In addition, Neffe‐Skocinska et al .…”
Section: Resultsmentioning
confidence: 99%
“…Moisture, total protein, crude fat, and nitrite were measured according to the methods reported by Bağdatli and Kundakci () and Wang and others ().…”
Section: Methodsmentioning
confidence: 99%
“…After 3 days of processing, the pH value was near 4.6 for all treatments, indicating that micro-organisms present in the fermenting starter culture produced lactic acid from the sugars present in the formulation, reducing the pH. Othes authors also reported a significant reduction of pH from day 0 to day 3 in the production of fermented sausage [11,12].…”
Section: Fig 1 Evolution Of Water Actitvy (A) Ph (B) and Weight Lomentioning
confidence: 88%